The Palestinian Question in Turkish Foreign Policy from 1990s to 2010s - BAYRAKTAR, BORA (Hale Şıvgın, 2019)
For several reasons the Question of Palestine has been closely followed by Turkey especially after the establishment of State of Israel. Turkey’s engagement with Palestinian territories is beyond her historical ties with it. At first, until 1990s, Palestinian issue served Turkish foreign policy to manage its relationship with the Arab World starting from 1960s. The other side of the coin was Turkey’s strained relations with Israel. The Oslo Peace Process between Israel and Palestinians enabled Turkey to boost its relations with Israel, reaching level of military partnership. After 2000s, Turkey’s balanced Palestinian policy has been dramatically changed and Turkey apparently became the leading advocate of “the Palestinian cause.” This article focuses on the evaluation of Turkey’s Palestinian policy and the logic behind it.

Filistin Sorunu özellikle İsrail Devleti’nin kuruluşundan itibaren çeşitli nedenlerden dolayı Türkiye tarafından yakından izlenmektedir. Türkiye’nin Filistin toprakları ile bağı bu coğrafya ile tarihi bağlarından öte anlamlar içermektedir. 1960’lardan 1990’lara kadar Filistin Sorunu Türk dış politikasında Arap dünyası ile ilişkileri düzenlemekte bir araç olarak öne çıkmıştır. Filistin sorunu Türkiye’nin İsrail ile sorunlu ilişkilerinin de sebepleri arasındadır, Türkiye’nin Batı ile ilişkileri açısından referans olmuştur. 1990’lardaki İsrail ile Filistinliler arasındaki Oslo Barış Süreci Türkiye’nin İsrail ile ilişkilerinin gelişmesini ve askeri ortaklığa kadar ilerlemesini sağlamıştır. 2000’li yıllardan itibaren İkinci İntifada ile birlikte Türkiye’nin yürüttüğü denge politikası kökten değişmiş ve Türkiye “Filistin Davası’nın” önde gelen savunucularından biri haline gelmiştir. Bu makale Türkiye’nin Filistin politikasındaki değişimi ve bunun arkasındaki düşünceyi açıklamaya çalışmaktadır.
Türk Dış Politikası’nda Filistin Sorunu 1990’lardan 2010’lara
Keywords: Turkey; Palestinian Policy; Israel; Turkish Foreign Policy; Middle East